Effects of liver transplantation on endocrine function: a systematic review. (23rd June 2016) - Gariani, Karim; Toso, Christian; Philippe, Jacques; Orci, Lorenzo A.
Abstract: Patients with chronic liver disease (CLD) often experience secondary endocrine dysfunction. Therefore, because the liver plays a major role in endocrine function, liver transplantation (LT) may also be beneficial for the restoration of hormonal regulation. This systematic review collects and interprets the available literature on the effect of LT on endocrine and sexual function in adult patients. A systematic review was conducted by searching Pubmed (including Medline) and EMBASE for studies published from database inception until November 2015. We collected all relevant studies that discussed changes in hormonal and sexual function after LT. Studies were included if they assessed the effect of LT on sexual function or one of the following components of the hormone/endocrine axis: the hypothalamus–pituitary–gonadal axis, growth hormone (GH), insulin‐like growth factor‐1 (IGF‐1) or thyroid function. The results are reported according to the Meta‐analysis Of Observational Studies in Epidemiology (MOOSE) guidelines. Twenty‐one studies with a total of 1274 patients were included. The results collected from the included studies suggested that LT improves the hormonal perturbation associated with CLD by restoring physiological levels of circulating GH, IGF‐1, testosterone, estradiol, prolactin, follicle‐stimulating hormone (FSH) and luteinizing hormone (LH). Thyroid function was not affected by LT, and sexual function was partially improved after LT. This systematic review suggests that LT is associated with an improvement in endocrine and sexual function in patients with CLD. This information should encourage clinicians who treat CLD patients to identify endocrine disturbances in this population, inform their patients of the effects of LT and assess post‐transplantation improvements.